1993
DOI: 10.1093/jn/123.11.1888
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Folate Requirement Determined for Channel Catfish, Ictalurus punctatus

Abstract: Juvenile channel catfish, Ictalurus punctatus, were fed semipurified basal diets containing 0, 0.2, 0.5, 1.0, 4.0 or 10.0 mg/kg of folic acid or 10 g/kg of succinylsulfathiazole in aquaria for 15 wk. Fish fed the sulfonamide showed higher mortality, lower weight gain, lower thrombocyte counts, higher hemocytoblast and neutrophil counts, and lower liver folate concentrations than did control fish (0 folic acid), indicating that significant intestinal bacterial synthesis of folate occurs in channel catfish. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 20 publications
4
29
0
1
Order By: Relevance
“…Our findings agreed with the reports on optimal dietary folic acid requirement of grass shrimp (Shiau and Liu, 1994;Shiau and Chin, 1998;Shiau and Chen, 2000), juvenile (Shiau and Huang, 2001b), rainbow trout (Cowey and Woodward, 1993;Esmaeili and Khara, 2014), Grouper (Lin et al, 2011), channel catfish (Duncan et al, 1993) Niletilapia (Barros et al, 2009), Piglets (Ying et al, 2013) Chinese mitten crab (Wei et al, 2015) and Blunt snout bream fingerlings (Sesay et al, 2016). These present investigation suggested that an enhanced growth by dietary folic acid might be a result of increased feed intake and efficiency in feed utilization.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings agreed with the reports on optimal dietary folic acid requirement of grass shrimp (Shiau and Liu, 1994;Shiau and Chin, 1998;Shiau and Chen, 2000), juvenile (Shiau and Huang, 2001b), rainbow trout (Cowey and Woodward, 1993;Esmaeili and Khara, 2014), Grouper (Lin et al, 2011), channel catfish (Duncan et al, 1993) Niletilapia (Barros et al, 2009), Piglets (Ying et al, 2013) Chinese mitten crab (Wei et al, 2015) and Blunt snout bream fingerlings (Sesay et al, 2016). These present investigation suggested that an enhanced growth by dietary folic acid might be a result of increased feed intake and efficiency in feed utilization.…”
Section: Discussionsupporting
confidence: 92%
“…Folic acid requirement has been studied in some fish and crustacean species including tilapia (Shiau and Huang, 2001a), green cat fish (Hien and Doolgindachbaporn, 2011), rainbow trout (Cowey and Woodward, 1993), grouper (Lin et al, 2011), channel catfish (Duncan et al, 1993) and penaeids (Shiau and Huang, 2001b). Folic acid deficiency has an adverse effect on fish and crustacean growth and health including signs of macrocytic normochromic anemia, poor growth, anorexia, general anemia, lethargy, caudal fin fragility, dark skin pigmentation, dark coloration and infarction of spleen (Halver, 1980;Shiau and Huang, 2001b).…”
Section: Introductionmentioning
confidence: 99%
“…Megaloblastic anaemia with large fragmented cell nucleus in erythrocytes Atlantic salmon (Sandnes 1994;Waagbø, 2010) Channel catfish (Duncan et al 1993) Coho salmon (Smith 1968;Smith & Halver 1969) Rainbow trout (Kitamura et al 1967) Rohu (John & Mahajan 1979) Changed skin coloration Darker colour than normal Japanese eel (Arai et al 1972) Changed behaviour Abnormal swimming Rainbow trout (Kitamura et al 1967) Lethargy…”
mentioning
confidence: 99%
“…The small lymphoid haemoblast and the basophilic erythroblast depicted by Mahajan & Dheer (1980) as first phases of erythropoiesis have characteristics of cells described here as prolymphocyte and lymphocyte. Haemoblasts of Weinberg et al (1972) and Grizzle & Rogers (1976) as well as the haemocytoblasts in figures of Duncan et al (1993) would be classified here as proerythroblast, basophilic and occasionally as polychromatic erythroblast. Erythroblasts I and II described by Lehmann & Stü renberg (1975) as well as the erythroblast and proerythrocyte of Blüm et al (1988) seemed to be identical with basophilic and polychromatic stages described in the present.…”
Section: Maturation Stages and Nomenclaturementioning
confidence: 98%